Precisão de plantas planialtimétricas em função do posicionamento de pontos em irradiadas de campo - Gomes, Luciano Nardini [UNESP]; Cardoso, Lincoln Gehring [UNESP]; Barros, Zacarias Xavier de [UNESP]; Campos, Sérgio [UNESP]; Rodrigues, Vilmar Antônio [UNESP] (My University, 2006)
The present experiment aimed to study the influence of point positioning in an irradiated field to produce a planialtimetric plant. A planialtimetric evaluation was carried out in a 14-acre experimental area with well-defined topographic variations. Planialtimetric maps were designed using manual procedures, Datageosis and Topoesalq. Datageosis built all the curves after numerical surface modeling. Topoesalq provided only height reports and the drawing of curves was done manually. The third method was a manual procedure. Because there were planialtimetry representation differences, longitudinal profiles were used in the sites where there was a great divergence among plants. When obtained profiles and plants were compared, it was verified that the one produced by Datageosis represented the relief plant better. Later, only the irradiated field points were evaluated and each point presented positioned readings before and after each relief map variation. The processing through the three methods resulted in significant plants of the local planialtimetry, according to the control profiles. It was concluded that the planning of the field procedure should be suitable to the posterior treatment method of obtained data in order to make a planialtimetric plant to accord to the evaluated local topography.
Accuracy of planialtimetric plants according to point positioning in an irradiated field
Keywords: Numerical surface modeling; Planialtimetry; Evaluation; Maps; Mathematical models; Planimeters; irradiation; numerical model; plant